Financial Feasibility Analysis of Rhizosphere Restoration For Stevia (Stevia Rebausidiana Bertoni M) Cultivation at Sugar Group Companies Lampung - Jonathan Jusuf; Azwar Maas; Slamet Hartono (Agro Ekonomi, 2018)
The research objectives are to (i) analyze the effects of restoring the growth medium (rhizosphere) toward the production of stevia leaves and (ii) analyze the financial likelihood to restore the growth medium (rhizosphere). The data necessary to answer objective 1 and 2 was retrieved from field research utilizing plot research method along with Complete Randomized Group Design (CRD) comprised of 15 x 2 executions and 3 replications. The plot size used was 2m x 0,6m (1,2m2). Research shows that rhizosphere restoration is able to increase the production of dry stevia leaves. The effort to restore rhizosphere can increase dry stevia leaf production. Financial likelihood analysis of rhizosphere restoration shows that B/C ratio is greater than one, NPV is greater than zero, IRR is quite large at 20%, Unit BEP and Price BEP was exceeded, showing that rhizosphere restoration is financially beneficial. However is still sensitive toward changes of benefit and cost. This research suggests that the increase of dry stevia leaf production should be increased even higher.